Una svolta drammatica. Somiglianza ed empatia tra Medioevo e contemporaneità - Bino, Carla (Scenari, 2021)
This paper seeks to frame the importance of ‘imaginative culture’ during the Middle ages. In the first part, I provide an overview of the most recent works on the medieval vision theories, underling the increasing interest of medieval scholars in visual culture and cognitive theory. In the second part, starting with the theory of image formulated by theology and exegesis between the 3th and the 11th century, I illustrate the key elements of the visual culture of the Middle Ages and I argue that it is founded on a real ‘dramatic turn’, whose peculiar features are the close connection between vision and action, the performative inclusion and, finally, the empathetic knowledge.